Design thinking na publicidade: uma proposta de ensino-aprendizagem para estudantes de graduação - Souza, Amarinildo Osório de (2018)
This work consists of a teaching-learning proposal for the development of advertising projects with Design Thinking (DT), aimed at undergraduate students in Marketing and Advertising. DT is used in the business world for innovation, research and development of products and services in different applications, being an emerging theme in other areas of knowledge, such as education, where it has also been used for different purposes. It is an approach that follows a process organized in phases, based on a culture of values and tools that make it possible to understand a problem from different perspectives and to generate projects in which the main focus is people. In this research, the general objective was to evaluate the application of Design Thinking in the development of advertising projects, specifically as it relates to improvements in information gathering, idea generation and solution building, considering students of a Superior Course in Technology in Advertising Production (CSTPP). It is a qualitative research that adopted as a research strategy the action research to organize the methodological procedures by means of three (03) steps (planning, implementation and evaluation), having as instruments of data collection: questionnaires, field diary and the publicity projects constructed with the participants. The teaching-learning proposal was applied in the form of an extension course, in February 2018, combining activities of face-to-face and autonomous study on the fundamentals, phases, values and tools of the DT. The participant students, selected through a public notice, were 15 (fifteen) students of the Superior Course of Technology in Advertising Production (CSTPP) of the Federal Institute of Education, Science and Technology of Amazonas - Manaus Campus Center. Organized in teams, the participant students, under the guidance of the researcher-participant, developed four (04) advertising projects through the three phases of the DT: immersion, ideation and prototyping. These projects were evaluated through a set of criteria organized in rubrics, thus establishing the level of participant students performance, difficulties and improvements observed during each phase. The results showed that DT improved the skills for information gathering, generation of ideas and validation of projects, through prototyping and feedback´s colect. However, it pointed to the immersion phase as the one in which the participant students had greater difficulty of execution, besides limitations verified in the management of the collaborative work in team and autonomous study. Synthetic thinking is a point to be verified in future studies, in order to better understand these limitations and to promote notes that can improve this ability for students and professionals of Marketing and Advertising. As a result of this research, an educational product was organized, a Teaching Guide under the title "DT in Advertising: a teaching-learning proposal for the development of advertising projects with Design Thinking", which includes the detailing of the teaching-learning proposal, didactic resources and a set of guidelines that helps teachers and students in the area of Marketing and Advertising for the replication of said proposal in their teaching contexts.